Magnetoelectric coupling at metal surfaces - Gerhard, Lukas Leander (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2013)
Nowadays, the development of magnetic data storage devices technique faces fundamental limitations which lead to a slow-down of the increase of areal storage density. Therefore, magnetoelectric coupling which allows to change the magnetic state of matter by means of an electric field attracted significant interest. In this work, scanning tunneling microscopy was used to show for the first time that magnetic information can be written on the nanometer scale by the application of electric fields.